Glycemia level and temperature at discharge, of term newborns of the National Maternal Perinatal Institute, 2019 - Quispe-Condori, Custodio Olsen (2023)
Objective. To determine the association between temperature and blood glucose level at discharge in exclusively breastfed term newborns from the Joint Hosting Service of the National Maternal Perinatal Institute. Materials and methods. Analytical, observational, prospective, case-control study. The group of cases consisted of 70 neonates with hypothermiaand the group of controls consisted of 140 neonates with normothermia, from the Joint Hosting Service E of the National Maternal-Perinatal Institute. The newborn who met the inclusion criteria was recruited and, with the informed consent of the mother, the newborn’s temperature, blood glucose and weight were taken. Results. The average length of life was 51.02 for the case group and 49.97 hours of life in the control group. The average temperature was 36.31°C in the casegroup and 36.9°C in the control group. Regarding glycemia in the case group the average was 56.33 mg/dL and in thecontrol group 63.5mg/dL, both with a p < 0.00. The measure of association between the two variables was an OR of 2.57with a 95% CI of (1.26-5.16) which was statistically significant. Conclusions. Neonates with hypothermia had lower mean blood glucose than neonates with normothermia, such difference was statistically significant.